(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Its durability, low cost and robustness, induction motors are the most popular electric motors. The induction motors, however, are not capable of variable speed operation automatically. This is why older dc motors were found in most electric drives. But modern advances in induction motor speed regulation methods have culminated in their wide-ranging usage in nearly all electric drives. The most frequently used closed loop constant V f speed control system is a multi-methods for induction power, such as polar shift, frequency variance, variable rotor resistance, variable stator voltage, constant Vf regulation, slip recovery method, etc. The V f ratio is kept constant in this system, which in turn holds the magnetizing stream constant to hold its maximal torque unchanged. The stator resistance and engine induction (both rotor and stator) should be held low while an induction motor is started to minimise the stable state period and also to avoid jerks during initialization. On the other side, a higher rotor resistance value contributes to fewer jerks and has little effects on the continuous condition duration. The induction vector control research allows for a decoupling research in which the torque and the flow components can be regulated separately (just as in the dc motor). This simplifies the study than the identical circuit per step.